Political leadership change: A theoretical assessment using a human capital “learning by doing” model - Sousa, Miguel Rocha de (2013)
We present an economic growth model with human capital, based upon Arrow (1962), in which we assess the impact of political leadership change either in governments or political parties. The change of leadership might be seen as a change in embedded human capital, and thus we might evaluate the loss or gain for society due to these political activities. The approach is theoretical using Arrowian economic setting. We formulate the conditions in which it is worth it, or how long does it take to recover from a political leadership change. The embedded process is an economic one, known as “learning by doing”, but this time applied to political processes.